Impact of cold storage on the oxygenation and oxidation reactions of red blood cells - Kassa, Tigist; Jana, Sirsendu; Baek, Jin Hyen; Alayash, Abdu I. (Frontiers in Physiology, 2024)
Electrostatic binding of deoxyhemoglobin (Hb) to cytoplasmic domain of band 3 anion transport protein occurs as part of the glycolytic regulation in red blood cells (RBCs). Hb oxidation intermediates not only impact RBC’s oxygenation but also RBC’s membrane through the interaction with band 3. It is not known however whether these critical pathways undergo changes during the storage of RBCs. Oxygen parameters of fresh blood showed a sigmoidal and cooperative oxygen dissociation curve (ODC) for the first week of storage. This was followed by a large drop in oxygen affinity (P50) (from 30 to 20mmHg) which remained nearly unchanged with a slight elevation in Bohr coefficients and a significant drop in extracellular acidification rates (ECAR) at the 42-day storage. Oxidation of Hb increased with time as well as the formation of a highly reactive ferryl Hb under oxidative stress conditions. Ferryl Hb interacted avidly with RBC’s membrane’s band 3, but to lesser extent with old ghost RBCs. The observed alterations in RBC’s oxygen binding may have been affected by the alterations in band 3’s integrity which are largely driven by the internal iron oxidation of Hb. Restoring oxygen homeostasis in stored blood may require therapeutic interventions that target changes in Hb oxidation and membrane changes.